2018
DOI: 10.1016/j.juro.2018.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and Risk of Kidney Stones

Abstract: Postmenopausal status is associated with a higher risk of incident kidney stones. Natural menopause and surgical menopause are independently associated with higher risk. There are small but significant differences in urine composition between premenopausal and postmenopausal urine collections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 14 publications
5
28
0
Order By: Relevance
“…Our study also demonstrated the demographic differences between premenopausal and postmenopausal women with urolithiasis. Despite the relatively low number of patients in our study, the nding that postmenopausal women had a higher prevalence of hypertension, lower BMD, and hypocitraturia was consistent with current evidence [27], implying that postmenopausal status was associated with a higher risk of urolithiasis.…”
Section: Discussionsupporting
confidence: 89%
“…Our study also demonstrated the demographic differences between premenopausal and postmenopausal women with urolithiasis. Despite the relatively low number of patients in our study, the nding that postmenopausal women had a higher prevalence of hypertension, lower BMD, and hypocitraturia was consistent with current evidence [27], implying that postmenopausal status was associated with a higher risk of urolithiasis.…”
Section: Discussionsupporting
confidence: 89%
“…The key nding in this study is that an signi cant difference in uCA-2 excretion by ELISA analysis could discriminate patients with urinary stones from healthy controls. If our results are supported by many prospective validation studies, such a test might be clinically bene cial in the surveillance of high-risk patients, such as patients with metabolic syndrome [1][2][3][4] , in ammatory bowel disease 18 and accepted bariatric surgery 19 et al High risk of stone recurrence patients may also reap the bene ts of our results.…”
Section: Discussionsupporting
confidence: 59%
“…A number of potential metabolic [1][2][3] , genetic [4][5][6] , drug-induced 7,8 , and epidemiological 9,10 factors for urolithiasis have been reported. The knowledge of these factors contributes in determining the most appropriate therapy for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we conclude that in China, those most likely to experience urolithiasis are of economically productive age, which could be associated with a high level of physical labour, excessive sweating, and low water intake. In two age subgroups 51–60 and 61–70 years, in which the ratio of male:female was <2, females submitted more stones than other age subgroups, which may be associated with menopausal oestrogen decline after the age of 50 years .…”
Section: Discussionmentioning
confidence: 93%